Safety evaluation of the food enzyme laccase from the non‐genetically modified Trametes hirsuta strain AE‐OR - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal)
Abstract The food enzyme laccase (benzenediol:oxygen oxidoreductase; EC 1.10.3.2) is produced with the non‐genetically modified Trametes hirsuta strain AE‐OR by Amano Enzyme Inc. The food enzyme is free from viable cells of the production organism. It is intended to be used in six food manufacturing processes. Dietary exposure to the food enzyme–total organic solids (TOS) was estimated to be up to 0.026 mg TOS/kg body weight (bw) per day in European populations. Genotoxicity tests did not raise a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 862 mg TOS/kg bw per day, the highest dose tested, which when compared with the estimated dietary exposure, resulted in a margin of exposure of at least 33,154. A search for the similarity of the amino acid sequence of the food enzyme to known allergens was made and no match was found. The Panel considered that a risk of allergic reactions by dietary exposure cannot be excluded, but the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.